Sustaining the honey industry all along the value chain - upgrading the production, processing and marketing - Othman, Mohd Shahwahid; Abdul Aziz, Yuhanis; S., Zaiton; Mardan, Makhdzir; Ishak, Azmi (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
The Muda and Pedu forest reserves are not only essential for their biodiversity and water resources regulator but suppliers of natural honey. Rural community teams climb Tualang trees to harvest natural honey from the wild Apis dorsata bee hives to be supplied to the FAMA Honey House, Kuala Nerang. Honey bees are essential for their pollinations of agricultural produces and livelihood of traditional rural folks. Potential sales from honey harvesting depend on the hives availability ranging from an average of 13 hives and a maximum of 30 hives per tree. Honey harvesting is a specialized profession involving a team with specialized tasks. Sales from natural honey harvesting is lucrative earning an average income of RM650 to as high as RM16,000 per team member but seasonal for only 1 to 2 months a year. Two interesting issues were identified. Firstly, how to sustain the traditional Tualang honey harvesting profession that only generates income for a short season. A program is needed to provided a more regular supplementary incomes to the profession. Secondly, the traditional honey harvesting is interesting and an eco & edu-tourism attraction to both local and international tourists. A programme is required to link it to the tourism package. A knowledge transfer programme is framed by UPM working in consort with FAMA. Six honey harvesting team members of the Muda and Pedu forest reserves were selected, and trained to participate into stingless bee (kelulut) apiculture farming and integrated into the traditional honey harvesting eco and edu-tourism package. Good marketing practices will be inculcated. The aim is to raise and sustain their income throughout the whole year. Another 4 team members will be identified soon to complete the team to 10 members. It is anticipated that this KTP project would raise rural folks income on a more regular and sustained basis.